Beyond Clinical Case Studies in Psychoanalysis: A Review of Psychoanalytic Empirical Single Case Studies Published in ISI-Ranked Journals - Meganck, Reitske; Inslegers, Ruth; Krivzov, Juri; Notaerts, Liza (Frontiers in Psychology, 2017)
Single case studies are at the origin of both theory development and research in the field of psychoanalysis and psychotherapy. While clinical case studies are the hallmark of psychoanalytic theory and practice, their scientific value has been strongly criticized. To address problems with the subjective bias of retrospective therapist reports and uncontrollability of clinical case studies, systematic approaches to investigate psychotherapy process and outcome at the level of the single case have been developed. Such empirical case studies are also able to bridge the famous gap between academic research and clinical practice as they provide clinically relevant insights into how psychotherapy works. This study presents a review of psychoanalytic empirical case studies published in ISI-ranked journals and maps the characteristics of the study, therapist, patient en therapies that are investigated. Empirical case studies increased in quantity and quality (amount of information and systematization) over time. While future studies could pay more attention to providing contextual information on therapist characteristics and informed consent considerations, the available literature provides a basis to conduct meta-studies of single cases and as such contribute to knowledge aggregation.